OP0211 Nintedanib Inhibits Fibroblast Activation and Ameliorates Fibrosis in Preclinical Models of Systemic Sclerosis. (9th June 2015) - Huang, J.; Beyer, C.; Zerr, K.P.; Zhang, Y.; Ramming, A.; Distler, A.; Gelse, K.; Distler, O.; Schett, G.; Wollin, S.L.; Distler, J.H.
Abstract : Background: Nintedanib is a multi-tyrosine kinase inhibitor that targets several pro-fibrotic pathways such as platelet derived growth factor receptor (PDGFR)-α and β, fibroblast growth factor receptor (FGFR)-1, 2, 3, vascular endothelial growth factor receptor (VEGFR)-1, 2, 3 and Src-family kinases Src. Nintedanib thus offers potential to simultaneously target multiple pro-fibrotic pathways in SSc. Nintedanib has been shown to slow disease progression in idiopathic pulmonary fibrosis in two replicate phase III clinical trials and has recently been approved by the FDA for the treatment of idiopathic pulmonary fibrosis (IPF). Objectives: The aim of this study was to analyze the anti-fibrotic effects of nintedanib in preclinical models of systemic sclerosis (SSc). Methods: The effects of nintedanib on migration, proliferation, myofibroblast differentiation and release of extracellular matrix of dermal fibroblasts were analyzed by MTT- and scratch assays, stress fiber staining, qPCR and SirCol assays. The anti-fibrotic effects of nintedanib were evaluated in bleomycin-induced skin fibrosis, in murine sclerodermatous chronic graft-versus host disease and in tight-skin-1 mice at 30 mg/kg qd, 60 mg/kg qd and 50 mg/kg bid. Results: To assay the effects of nintedanib on migration and proliferation of fibroblasts, scratch assays were performed. Nintedanib delayed the PDGF- and TGFβ-induced closure of the scratch in a concentration-dependent manner. Nintedanib also inhibited proliferation of fibroblasts in MTT assays. Moreover, nintedanib dose-dependently reduced the mRNA levels of Col 1a1, Col 1a2 and fibronectin-1 as well as the release of collagen protein into the supernatant and decreased the basal levels of αSMA and of stress fibers in cultured fibroblasts from SSc patients in the absence of exogenous stimuli as well as upon incubation with TGFβ or PDGF. Nintedanib exerted potent anti-fibrotic effects in a variety of complementary mouse models. Treatment with nintedanib dose-dependently ameliorated dermal thickening, myofibroblast differentiation and collagen deposition in bleomycin-induced skin fibrosis, as a model of localized, inflammation-driven model of SSc, in a model of sclerodermatous chronic graft-versus host disease with systemic fibrotic changes as well as in tight-skin-1 mice resembling later stages of SSc with endogenous activation of fibroblasts. Maximal anti-fibrotic effects were observed with nintedanib in pharmacologically relevant doses of 50 mg/kg bid. Of note, treatment with nintedanib was effective in preventive as well as in therapeutic settings. Conclusions: Nintedanib effectively inhibits the endogenous as well as cytokine-induced activation of SSc fibroblasts and that nintedanib exerts potent anti-fibrotic effects in complementary mouse models of SSc. The potent anti-fibrotic effects of nintedanib provide a scientific rational for clinical trials with nintedanib in SSc. Disclosure of Interest: None declared